Особливості опорно-скоротливого апарату селезінки хребетних тварин - Дунаєвська, Оксана; Dunaіevska, Oksana (Східноєвропейський національний університет імені Лесі Українки, 2016)
На основі гістологічних досліджень установлено морфометричні особливості опорно-скоротливого апарату селезінки хребетних тварин. З’ясовано, що в риб радіальні трабекули слаборозвинені, у жаби та ящірки вони відсутні. Опорно-скоротливий апарат займає від 3,02 до 13,64 % відносної площі селезінки. Найбільш розвинений він у коней, овець і свиней.On the basis of histological research was set the morphometric characteristics of the splenic support-contractile apparatus in vertebrates. Smooth muscle tissue in the connective tissue through the spleen is best developed in dogs, horses, and least of all in the rabbit. The support-contractile apparatus takes 3,02 % (chickens) to 13,64 % (the horse) of relative spleen area. It is the most developed in horses, sheep and pigs. The trabecular apparatus prevails in the stroma of most animals except frogs and rabbits. Splenic trabeculae are distinguished vascular and radial connection. In birds, lizards and frogs capsular trabeculae are not identified; they got weak development in fish and rabbit. The average value thickness of the splenic capsule is between 21,85 ± 7,44 micrometers in fish to 193,86 ± 107,84 micrometers in horses. The thickness of the capsule varies in different parts of organ, it is the most developed in the gate, all over its surface is met a thickening, often superior to the capsule thickness in 2–3 times. The thinnest capsule is located on the visceral surface of the spleen.
The Features of Splenic Support-contractive Apparatus in Vertebrates.
Keywords: селезінка; колагенові й еластичні волокна; трабекули; капсула; spleen; collagen and elastic fibers.; trabeculae; capsule